2020
DOI: 10.3389/fchem.2020.507887
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Flavonoids From Natural Sources Using Modern Techniques

Abstract: Flavonoids are one of the main groups of polyphenols found in natural products. Traditional flavonoid extraction techniques are being replaced by advanced techniques to reduce energy and solvent consumption, increase efficiency and selectivity, to meet increased market demand and environmental regulations. Advanced technologies, such as microwaves, ultrasound, pressurized liquids, supercritical fluids, and electric fields, are alternatives currently being used. These modern techniques are generally faster, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
242
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(257 citation statements)
references
References 191 publications
(278 reference statements)
10
242
0
5
Order By: Relevance
“…The sample–solvent ratio is also a crucial factor with regards to production capacity since they have a direct influence on the cavitation phenomenon and on the final concentration of the extracts [ 46 ]. According to Chaves et al [ 47 ], when the objective of the extraction is the preparation of samples for quantitative analysis, high solvent ratios (1:50, 1:100, or even higher) may be required to ensure that the target compounds are entirely removed from the sample matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The sample–solvent ratio is also a crucial factor with regards to production capacity since they have a direct influence on the cavitation phenomenon and on the final concentration of the extracts [ 46 ]. According to Chaves et al [ 47 ], when the objective of the extraction is the preparation of samples for quantitative analysis, high solvent ratios (1:50, 1:100, or even higher) may be required to ensure that the target compounds are entirely removed from the sample matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The phase equilibrium plays an essential role during the designing of a highly sensitive process with too many operating conditions to be followed. A large amount of pressure and environmental conditions also need to be met for the initiation of separation studies (Chaves et al 2020).…”
Section: Supercritical Fluid Extractionmentioning
confidence: 99%
“…Microwaves consist of electric and magnetic fields that oscillate perpendicularly to each other in a high-frequency range from 0.3 to 300 GHz [24,32]. This condition produces localized heating and causes the destruction of the plant matrix leading, to the easier diffusion of the compounds of interest into the solvent [28,32]. A microwave power between 300 and 900 W and extraction temperatures ranging from 50 to 100 • C are generally used [19].…”
Section: Microwave-assisted Extraction (Mae)mentioning
confidence: 99%
“…Regarding the extraction conditions, studies have shown that ASE is more efficient when mixtures of solvents are used, such as methanol or ethanol in water, instead of pure solvents [19], for the reasons of polarity compatibility. Working pressures ranging from 4 to 20 MPa affect the diffusion of the solvent into the pores of the raw material matrix, enhancing the contact of the target compounds with the solvent [32,38]. Temperature is also an important parameter of ASE extraction.…”
Section: Accelerated Solvent Extraction (Ase)mentioning
confidence: 99%
See 1 more Smart Citation